Mononuclear Lanthanide Complexes: Energy‐Barrier Enhancement by Ligand Substitution in Field‐Induced DyIII SIMs. Issue 20 (23rd August 2022) - Gao, Yu; Yang, Peipei; Hu, Yiye; Zhang, Mengyuan; Zhu, Xinxin; Liu, Yalin
Abstract: Four mononuclear complexes were synthesized through simple self‐assembly reactions, [Dy(L1 )2 (NO3 )H2 O] (1), [Tb(L1 )2 (NO3 )MeOH] (2), [Ho(L1 )2 (NO3 )H2 O] ⋅ 5.5H2 O (3) (HL1 =4‐bromo‐2‐((quinolin‐8‐ylimino)methyl)phenol), and [Dy(L2 )2 (NO3 )H2 O] (4) (HL2 =2, 4‐dibromo‐6‐((quinolin‐8‐ylimino)methyl)phenol). They are characterized by their structures and magnetic properties. The magnetic data show that the Dy clusters all have obvious frequency‐dependent magnetic behavior and slow magnetic relaxation effects. The complex 1 under an external dc field with the anisotropic barrier of 14.41 K and pre‐exponential factor τ0 =2.70×10 −6  s, the complex 4 under an external dc field with the anisotropic barrier of 64.36 K and pre‐exponential factor τ0 =2.38×10 −7  s. Abstract :